THEORETICAL AND ORGANIZATIONAL FUNDAMENTALS OF IMPLEMENTATION OF REPUTATION MANAGEMENT IN THE COMPANY - Shkromyda , V.V. (The actual problems of regional economy development, 2020)
The trend in recent decades has been characterized by a growing interest of business representatives in their reputation and its impact on performance and, consequently, development for the future. Awareness of the importance and value of the latter among the leadership of most business structures, there is a need in various ways and means to build an unquestionable reputation, strengthen among stakeholders and use it effectively. Of course, achieving this goal is possible through the introduction of reputation management. The implementation of an effective reputation management system in the course of the business entity must be confirmed by obtaining the expected results from the implementation of such management measures. Certainly, the implementation and realization of reputation management provides usefulness and a number of advantages for the company, which allow to develop an impeccable reputation and gain favorable loyalty among the external business environment. The study proved a key feature of business reputation, which is expressed by the «object-subjective» relationship. The binary nature of this feature is explained by the transition of the object to the subject and, in other circumstances, vice versa. Among the elements of the theoretical and organizational foundations of the implementation of reputation management in the enterprise, increased attention is paid to the study of the attributes of its business reputation. It is established that a detailed study of the structural content of the company's reputation will help to design it taking into account the specifics of the activity and the peculiarities of the business environment. The practical value of the research is to supplement the theoretical and methodological basis of reputation management, in particular in terms of its implementation in the activities of companies. We believe that the obtained scientific results will contribute to the development of an effective mechanism for information support of the reputation management system of the business entity.